An Investigation Into Physical Frailty as a Link Between the Gut Microbiome and Cognitive Health - Verdi, Serena; Jackson, Matthew A.; Beaumont, Michelle; Bowyer, Ruth C. E.; Bell, Jordana T.; Spector, Tim D.; Steves, Claire J. (Frontiers in Aging Neuroscience, 2018)
The preservation of cognitive abilities with ageing is a priority both for individuals and nations given the ageing populations of many countries. Recently the gut microbiome has been identified as a new territory to explore in relation to cognition. Experiments using rodents have identified a link between the gut microbiome and cognitive function, particularly that low microbial diversity leads to poor cognition function. Similar studies in humans could identify novel targets to encourage healthy cognition in an ageing population. Here we investigate the association of gut microbiota and cognitive function in a human cohort considering the influence of physical frailty. We analyzed 16S rRNA gene sequence data, derived from faecal samples obtained from 1551 individuals over the age of 40. Cognitive data was collected using four cognitive tests: verbal fluency (n= 1368), Deary-Liewald Reaction Time Test (DLRT) (n=873), Mini Mental State Examination (recall) (n=1374) and Paired Associates Learning from the Cambridge Neuropsychological Test Automated Battery (CANTAB PAL) (n=405). We use mixed effects models to identify associations with alpha diversity, operational taxonomic units (OTUs) and taxa and performed further analyses adjusting for physical frailty. We then repeated the analyses in a subset of individuals with dietary data, also excluding those using medications shown to influence gut microbiome composition. DLRT and verbal fluency were negatively associated with alpha diversity of the gut microbiota (FDR p<0.05). However, when considering frailty as a covariate, only associations between the DLRT and diversity measures remained. Repeating analyses excluding PPI and antibiotic users and accounting for diet, we similarly observe significant negative associations between the DLRT and alpha diversity measures and a further negative association between DLRT and the abundance of the order Burkholderiales that remains significant after adjusting for host frailty. This highlights the importance of considering concurrent differences in physical health in studies of cognitive performance and suggests that physical health has a relatively larger association with the gut microbiome. However, the frailty independent cognitive-gut microbiota associations that were observed might represent important targets for further research, with potential for use in diagnostic surveillance in cognitive ageing and interventions to improve vitality.